Thermal explosion reaction coating on diamond surface of Cr/Al/B/diamond system - Jingxian HAN; Jialin LIU (Jin'gangshi yu moliao moju gongcheng, 2022)
Cr/Al/B/diamond powder was used as raw material, and a small amount of Cr2O3 or B2O3 was added to induce thermal explosion reaction. The results show that under the protection of high-purity Ar, the sample after thermal explosion reaction is seriously powdered, and it is easy to separate the binder from the diamond particles. After the thermal explosion reaction of the raw material system added with Cr2O3, the main phase in the binder is Cr2AlB2, and the composite coating containing Cr3C2 and Al will be formed on the diamond surface. The grain size of the composite coating is 0.5～7.0 µm. When the mass fractions of diamond are 10% and 20%, the surface of diamond particles in the samples are well coated, and the initial and the final oxidation temperatures of coated diamond are significantly higher than that of uncoated diamond. However, when the mass fraction of diamond is high, the coating effect on the diamond surface is slightly poor. After the thermal explosion reaction of the raw material system added with B2O3, the coating effect on the diamond surface is poor, and only half or less of the diamond particles are coated.